Nollywood and Churches’ Oriental Fantasies: Its Impact on Art Reception, Patronage and Expression in Contemporary Nigeria - Clement Emeka Akpang (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The visual arts still suffer low reception and patronage in contemporary Nigeria as a result of an ongoing oriental stereotypical representation in Nollywood, the media and churches. This paper interrogates this problematic to address the subtle subversion of the arts that continues to grossly impede its development. Adopting the analytical tools of Content Analysis, this paper traces the origin of anti-art propagandism to missionary and colonial activities in Nigeria and establish its continues adverse propagation in Nollywood and modern churches. Findings from this paper conclude that the portrayal of visual arts in Nigerian movies as the instrument of dark practices and the further condemnation of the arts in churches as symbols of heathenism is responsible for the disdain towards the arts in contemporary Nigeria and responsible for its poor reception and patronage. The research contends, therefore, that both the media, Nollywood and churches must rethink their oriental fantasies about the arts because until that happens the anti-art culture inscribed in the consciousness of many Nigerians will continue to impede artistic progress and visual/aesthetic illiteracy.